Search for Identity in Michael Ondaatje's Post colonial Novel In the Skin of a Lion - ايناس صبحي عامر وئام صلاح غازي (College of Education for Women, 2019)
In his post colonial novel, In the Skin of a lion, the Canadian/Sri Lankan writer, Michael Ondaatje is so interested in the term "Post colonialism" because he wants to show that the term doesn't only refer to a period of time that comes after colonialism. In other words, post colonialism is not only referred to as a literal description of formerly colonial societies. He deals with the termas a literary genre and an academic construct that describes the global conditions of a man after a period of colonialism. He shows that post colonialism is a theory that tries to examine and explore the different styles and faces of European authority to control the colonized. Ondaatje's attempt through such term is to unmask European authority and to focus on those who are excluded such as the immigrants and the outsiders who feel lost and without identities in their world. Thus, he writes In the Skin of a Lion to retell and illuminate the story of the marginalized characters of Toronto who are used and controlled by the colonizers to build Toronto but they remained as outsiders. The writer tries to weave the story around such characters as Caravaggio the thief, Nicholas Temelcoff the daredevil, Patrick the tunnel worker, and Alice the nun to show how the colonial powers dominated over them, marginalized and alienated them in a city where they sought home. He shows how the barriers of language, culture and beliefs hold these individuals back and imprison them in "the tunnels and the stockyards". They were denied even the right to communicate in their own language. This is because of the " rule of the city", a city that imposes on them their philosophies and values on struggling. It made them known only by their trade, "A starrer of roads, a house builder, a painter, a thief". Ondaatje resorts to The Epic of Gilgamesh to suggest thematically the title of his novel as In the Skin of a Lion. He emphasizes the idea of assuming the skin of a lion to take action because each one has responsibility in life. To sum up, the novel is a call to provide the opportunity for the once marginalized persons to stand and to be heard. In other words, the novel is about the transformation of identities in the shed of the colonialism.